The Indonesian Government's Legal Policy on the Presence of Illegal Migrants: Modus Operandi of Rohingya Migration in Aceh - Gaussyah, M.; Usman, Bustami; Mirja Fauzul Hamdi; Rizky Aulia Fitri (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The prolonged conflict in Myanmar between the government and the Rohingya ethnic group has caused a flow of refugees and illegal migration out of Myanmar. The ASEAN region that serves as a transit point and destination country for these illegal immigrants is Thailand, Malaysia, and Indonesia. This study uses an empirical research method analyzed with a legislative approach. Data was obtained through in-depth interviews and studies of legal regulations or legislation. The study concluded that illegal migrants who entered Aceh under the guise of being political asylum seekers who were stranded in Indonesian waters or land in need of assistance, this was indicated by the damage to the illegal migrants' boats, either intentionally damaged or indeed damaged. In the context of constitutional law, the central government's policy regarding the presence of refugees, including illegal Rohingya migrants, is to amend Presidential Decree Number 125 of 2016 concerning the Handling of Foreign Refugees. It is hoped that the revised Presidential Regulation will provide detailed regulations, particularly regarding status determination, refugee residency period, refugee criteria, the roles and responsibilities of stakeholders, the establishment of the PPLN Task Force, the fulfillment of the rights of foreign refugees in Indonesia and the use of budgets by Regional Governments, the sharing of burdens and responsibilities with International Organizations (IOs), and other matters that can improve the quality of handling foreign refugees. Some of the Indonesian Government's efforts to address illegal Rohingya migrants include increasing sea patrols, implementing a turn-back boat policy, establishing a main Indonesian Navy base (Lantamal) in Aceh, and involving the community, particularly the Panglima Laot (the Indonesian Navy Commander).